Organizational Agility-Oriented Management as a Response to the Dynamics of the Business Environment - Sujoko Sujoko (PT. Hafasy Dwi Nawasena, 2026)
Contemporary business environments characterized by volatility, uncertainty, complexity, and ambiguity compel organizations to move beyond rigid bureaucratic management toward agility-oriented approaches. This study examines how agility-oriented organizational management serves as a strategic response to dynamic business environments by integrating digital systems, human and cultural dimensions, and strategic agility. A qualitative multiple case study design was employed to explore organizational practices that reflect agility orientation. Data were collected through semi-structured interviews, non-participant observations, and document analysis involving organizations that have implemented digital transformation, adaptive performance systems, and cultural changes. The data were analyzed using thematic analysis through open, axial, and selective coding to identify patterns across cases. The findings reveal that agility emerges from the alignment of three primary pillars: digital transformation and performance systems that accelerate decision-making, people and organizational culture that foster adaptive behaviors, and strategic agility that enables rapid resource reconfiguration. When these elements are integrated, agility becomes institutionalized as a management orientation rather than an operational practice. This integration enables organizations to respond quickly to environmental turbulence, enhance innovation capacity, and sustain competitiveness. The study concludes that agility-oriented management is a comprehensive and systemic approach that allows organizations to proactively and adaptively navigate continuous business environment changes.